Instrument Development for Talent Scouting Fencing Athlete Achievement Towards 2022. - NURUDDIN PRIYA BUDI SANTOSA (Universitas Tunas Pembangunan, 2012)
Nuruddin Priya Budi Santoso 2012. Instrument Development for talent scouting Fencing Athlete Achievement Towards 2022. This study aimed (1) to determine the indicators that can be used in the development of sports talent scouting instrument towards the achievement of fencing athlete 2022, (2) to determine the validity and reliability of the instrument talent scouting the sport of fencing to the achievements of 2022, (3) to determine the effectiveness of the instrument fencing sport talent scouting achievements towards 2022. This study is a research approach to research and development, the steps are as follows: (1) review the criteria of good tests, (2) analyzesport to be tested, (3) preview literature, (4) select test items, (5) Establish procedures, (6) peer review, (7) pilot study, (8) determine validity reliability Objectivity, (9) develop norms, (10) construct a test manual. From the results of theoretical analysis, the instrument can be chosen sport fencing talent scouting, includes: (1) test coordination / throwing a tennis ball catch, (2) arm muscle power tests / throw a basketball, (3) test the leg muscle power / jump upright, (4) test the agility / running back and forth, (5) test the speed / run 40 m, (6) tests the reaction time, (7) kinestetict perception tests, (8) flexibility tests, (9) test accuracy, (10) multi-stage test.